The development of creative abilities of pupils of preschool educational institutions in artistic activity - Nataliia Semenova; Viktoriia Klish (Vasyl Stefanyk Precarpathian National University, 2017)
In the article the features of development of creative abilities of children of preschoolage in artistic activity. In particular, a theoretically grounded organizational and pedagogicalconditions of development of creative abilities of children. Also defined the creativedevelopment of the child by means of visual activity. Key words: creativity, art, preschool age, sensory education.